Beginning OpenVPN 2.0.9 : build and integrate virtual private networks using OpenVPN - Feilner, Markus; Graf, Norbert (Birmingham, U.K. : Packt Pub., 2009)
'This is a practical guide to using OpenVPN for building both basic and complex Virtual Private Networks. It will save you a lot of time and help you build better VPNs that suit your requirements. While providing only necessary theoretical background, the book takes a practical approach, presenting plenty of examples. It starts with an introduction into the theory of VPNs and OpenVPN, followed by a simple installation example on almost every available platform. After a concise and ordered list of OpenVPN's parameters, we dive into connecting several machines in a safe way. The last third of the book deals with professional and high-end scenarios, and also mobile integration. After having read the whole book and followed and understood all the examples, you will be an expert in VPN, Security, and especially in OpenVPN Technology. This book was written for version 2.0.9 of OpenVPN, but all examples have been tested and run smoothly on version 2.1 too'--Resource description p.
Includes bibliographical references and index.
Keywords: Extranets (Computer networks)